Impact of Monetary Policy Fluctuations on Conventional and Islamic Banks in Malaysia: Evidence from ARDL Approach - Ali, Abdullahi Osman (International Journal of Economics and Financial Issues, 2021)
The purpose of this study to investigate the effect of monetary policy on conventional and Islamic banks. This study deployed autoregressive distributed lag (ARDL) model due to its appropriateness for small sample. Bond test result indicates that there is long run relationship among Islamic bank loans and its determinant and also conventional bank and its determinant at 1% significance level. Nevertheless, result from this study illustrates that there is significant negative impact of interest rate on Islamic bank loans in short run and although it is not significant in the long run. it also illustrates presence of significant negative impact of interest rate on conventional bank loans in the short run while there is significant positive impact on conventional bank loans in the long run. The outcome from this study led several policy implications; Firstly, overnight policy rate designed to influence day to day activities of financial institutions is effective in performing its function as short term predictor. Secondly, since the result supported impact of interest rate on Islamic bank loans which make necessary for the central bank to set up monetary policy that suits both banks while interest free banks needs to improve their risk management tools. Keywords: Autoregressive distributed lag, Base financing rate, Base lending rate, Overnight policy rate JEL Classifications: E5, E52 DOI: https://doi.org/10.32479/ijefi.9210